2B.04: FACTORS RELATED TO THE LINK BETWEEN URIC ACID AND SYSTOLIC BLOOD PRESSURE IN YOUTHS. (June 2015) - Torro, M.I.; Alvarez, J.; Aguilar, F.; Redon, P.; Lurbe, E.
Abstract : Objective: The present research was undertaken to analyze factors related to the link between uric acid (UA) and office blood pressure (BP) in normotensive, high-normal and untreated essential hypertensive youths. Design and method: Six hundred and forty three Caucasians of both sexes (321 females), of European origin, predominantly obese, from 6 to 18 years of age (mean age 11.7 2.4) were included. The subjects were divided into 3 groups: normotensives 559 (87%; 92 non-obese), high-normal BP 58 (9%; 19 non-obese) or hypertensives 26 (4%; 5 non-obese) according to the ESH office BP criteria (Lurbe et al, J Hypertens 2009). Fasting blood was obtained and glucose, insulin, lipid profile, and UA were assessed. Results: In relation to the general characteristics, there were no differences among groups regarding age, BMI, BMI-zscore, HDL and insulin. Uric acid increases across the BP range from normotensive to hypertensive groups. Controlling by age and sex, UA was significantly correlated with BMI (r = 0.180, p = 0.000), BMI Z-score (r = 0.175; p = 0.000), SBP (r = 0.20; p = 0.000), insulin (r = 0.23; p = 0.000), and HDL (r = -0.149; p = 0.000). In a multiple regression analysis office SBP, insulin, and HDL cholesterol were independent determinants of UA when age, sex, and BMI were included (r2 = 0.25). Office systolic BP was the main determinant of UA in a stepwise analysis. Even though UA was corrected by body size, UA/BMI ratio, systolic BP was the main determinant in boys (See figure). Figure. No caption available. Conclusions: Uric acid is associated with BP, independently of metabolic factors in boys. The clinical implications require further investigation.